System Dynamics Modeling of Sustainability, Animal Welfare, and Certification in the Luwak Coffee Industry - Pramadya Ramdhana; Ivonne Ayesha (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Luwak coffee, globally recognized yet ethically contested, represents one of Indonesia’s most distinctive and high-value commodities. Despite its reputation, production remains small-scale and constrained by sustainability challenges, animal welfare concerns, and supply chain inefficiencies. This study aims to analyze the structure and behavior of the civet coffee production system using a system dynamics approach. Causal loop diagrams and stock–flow models were constructed to simulate policy scenarios across population dynamics, animal health, coffee cherry availability, certification, and market reputation. The results indicate that civet population growth is positively influenced by improved health and reduced mortality, while stress levels decline under enhanced welfare practices. Certification and reputation emerge as reinforcing drivers of market acceptance but remain highly vulnerable to negative publicity regarding animal welfare. Scenario analysis demonstrates that sustainable habitat management, investment in certification, and ethical compliance not only strengthen green bean stocks but also enhance long-term production resilience. Conversely, stagnant sales trends highlight that production capacity alone is insufficient without consumer trust and reputational legitimacy. These findings imply that integrating welfare-based management, ecological sustainability, and certification-driven reputation building is essential to ensure the long-term viability and competitiveness of the civet coffee industry.